2016
DOI: 10.2147/jir.s108783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BODE index and its relationship with systemic inflammation mediated by proinflammatory biomarkers in patients with COPD

Abstract: IntroductionBODE index, a multidimensional grading system which is based on Body mass index, airway Obstruction, Dyspnea scale, and Exercise capacity, has been increasingly used for the evaluation of chronic obstructive pulmonary disease (COPD). Many of the systemic manifestations of COPD are shown to be mediated by elevated levels of proinflammatory biomarkers.ObjectiveWe aimed to investigate the relationship between the BODE index, its components, disease severity, and proinflammatory biomarkers like C-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Those results are in line with previously reported findings (eg, Moore et al6), demonstrating that PR can reduce hospital admissions for AECOPD. A number of researches2527 also showed a significant relationship between GOLD stages and the BODE index, and the capacity of exercise in patients was associated with the severity of COPD. It was confirmed that geriatric COPD rehabilitation in the setting of a nursing home may reduce hospital admissions in frail COPD patients and increase exercise tolerance as well.…”
Section: Discussionmentioning
confidence: 97%
“…Those results are in line with previously reported findings (eg, Moore et al6), demonstrating that PR can reduce hospital admissions for AECOPD. A number of researches2527 also showed a significant relationship between GOLD stages and the BODE index, and the capacity of exercise in patients was associated with the severity of COPD. It was confirmed that geriatric COPD rehabilitation in the setting of a nursing home may reduce hospital admissions in frail COPD patients and increase exercise tolerance as well.…”
Section: Discussionmentioning
confidence: 97%
“…Most of our subjects were hospitalised owing to an acute exacerbation, and this may have interfered with their ability or desire to eat. In some patients, inflammation is associated with an increase in REE ( 37 ) , which, in the presence of poor dietary intake, may contribute to impaired energy balance ( 13 ) . Many studies now show, however, that although acutely unwell patients have an increase in REE this is more than compensated for by a decrease in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more severely affected patients show more reduced respiratory and peripheral muscle strength and endurance, as well as more hypoxemia and symptoms of hyperinflation 4 during exercise than patients with mild COPD. 3,5 It is already widely accepted that physical training is an essential part of nonpharmacologic treatment in moderate to severe COPD and is considered a key point in pulmonary rehabilitation programs aimed at improving exercise capacity, reducing symptoms, and enhancing quality of life. 6,7 With physical training being widely recognized and accepted as a fundamental component of a rehabilitation process, exercise intensity is an important factor to considered to achieve satisfactory physiological gains and relevant clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%